2014
DOI: 10.1016/j.gaceta.2013.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of advanced disease and late presentation in new HIV diagnoses reported to the surveillance system in Spain

Abstract: Despite universal health care coverage in Spain, men, immigrants and people infected through drug use or heterosexual contact seem to be experiencing difficulties in gaining timely access to HIV care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
20
2
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 27 publications
7
20
2
5
Order By: Relevance
“…The difference between the studies may be due to the different origins of the immigrants. In the majority of the studies in Spain and Europe, immigrants, especially Africans, are diagnosed later than the autochthonous population [4][5][6][7]14,21,22]. When we analyzed only the sub-Saharan subset, the delayed diagnosis results from Spain were similar to those of our study [3].…”
Section: Mortalitysupporting
confidence: 80%
See 3 more Smart Citations
“…The difference between the studies may be due to the different origins of the immigrants. In the majority of the studies in Spain and Europe, immigrants, especially Africans, are diagnosed later than the autochthonous population [4][5][6][7]14,21,22]. When we analyzed only the sub-Saharan subset, the delayed diagnosis results from Spain were similar to those of our study [3].…”
Section: Mortalitysupporting
confidence: 80%
“…The high percentage of delayed diagnosis among patients in our cohort was higher than in most studies in Spain [3,6,7,[18][19][20]. In some cases, this difference can be explained by the definition of delayed diagnosis or differences in the study period.…”
Section: Mortalitycontrasting
confidence: 60%
See 2 more Smart Citations
“…According to the SINIVIH study in Spain, 48 % of new diagnoses were in fact a delayed diagnosis (less than 350 CD4) and 28 % advanced disease (less than 200 CD4). The profile of people who did not know their HIV status before diagnosis were patients younger than 25 years or those older than 44 years and who had heterosexual sex (7,8) . 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 Numerous studies developed in Spain have shown a high frequency of sexual risk behaviors among young heterosexuals and homosexuals (9)(10)(11)(12)(13)(14)(15), but few studies have examined the frequency of HIV antibody testing and determinants of delayed diagnosis (16).…”
mentioning
confidence: 99%